The Effect of Natural Feed Density Variation During Immersion on The Growth of Pearl Oyster (Pinctada maxima) Spat in Laboratory Conditions - Miranti, Sevia; Mukhlis, Alia; Syukur, Abdul (Jurnal Biologi Tropis, 2025)
Pearl oysters (Pinctada maxima) are fishery commodities with high economic value and are widely cultivated. The challenge in pearl oyster cultivation is the imbalance between nutritional needs and natural feed availability, which has the potential to inhibit growth, increase mortality risk, and reduce the quality of produced spat. This research aims to identify the optimal natural feed density to enhance cultivation success and reduce mortality rates during the critical phase. This research was conducted from February to August 2025 at the laboratory of PT. Mutiara Surya Indonesia, Sugian Village, Sembelia District, East Lombok Regency. The experimental research method used a completely randomized design (CRD) consisting of 5 treatments with 3 replications. Data collection was performed on day 0, day 10, day 20, and day 30. The research results showed growth for each immersion with density variations: treatment A (control, without immersion) showed growth reaching 0.30 mm, treatment B grew approximately 0.32 mm, treatment C grew approximately 0.35 mm, treatment D grew approximately 0.41 mm, and treatment E grew approximately 0.55 mm. The difference in pearl oyster spat size (0.12 mm) significantly affected the density variation differences, which significantly influenced (p>0.05) absolute growth, relative growth, and daily specific growth on days 10, 20, and 30. However, it did not significantly affect (p>0.05) survival rates. The values of absolute growth, relative growth, and daily specific growth showed that treatment E was the best.